Sheet pan science : 25 fun, simple science experiments for the kitchen table : super easy setup and cleanup - Heinecke, Liz Lee (Quarry Books, 2022)
Sheet Pan Science features 25 awesome, bubbling, colorful, fizzing, oozing science experiments that all fit on a standard sheet pan.